Anatomy Education in Sri Lanka. Do we need unclaimed bodies? - Chenthuran, T. (The Jaffna Medical Association, 2025)
Cadaver-based education is accommodated by medical institutions with the hope of producing medical practitioners with essential knowledge in anatomy which is deemed fundamental to manage the clinical problems in their day-to-day clinical practice. It appears that the contemporary anatomy education of many countries is in need of unclaimed bodies, despite controversies in their usage, to meet the educational standards prescribed by the medical institutions and national authorities. Medical institutions in Sri Lanka procure dead bodies for anatomical studies primarily, if not wholly, through voluntary body donation programmes. However, the Transplantation of Human Tissues Act (THTA) of 1987, a Sri Lankan legislative act, permits the use of unclaimed bodies for anatomical research. This manuscript aims to review the procurement of unclaimed bodies for anatomy education in historical contexts, as well as regulatory and ethical dilemmas associated with using them for anatomical studies, particularly in the case of cadaveric dissection.
Keywords: Unclaimed bodies; Anatomy; Body donation